TRANSFORMING STUDENTS' LOGICAL-CRITICAL THINKING IN PRIMARY EDUCATION BASED ON THE REQUIREMENTS OF INTERNATIONAL ASSESSMENT PROGRAMS (PISA, TIMSS) - Vakilova Zarina Zohid qizi (International Journal of Literature and Language Studies, 2026)
This article examines the problem of transforming the logical-critical thinking of students at the primary education stage based on the requirements of the international assessment programs PISA (Programme for International Student Assessment) and TIMSS (Trends in International Mathematics and Science Study). The purpose of the study is to determine the level of formation of logical-critical thinking skills in elementary students and develop a didactic transformation model aimed at its development by analyzing the first results of Uzbekistan's PISA-2022 and TIMSS-2023 studies. The study used comparative-analytical and content-analytical methods, analyzed international reports, national concept documents, and scientific literature.